An Analysis of Characterization of Will Traynor and Louisa Clark and the Idea of Compassionate Love in Me Before You (2016) - Yukiko Tirzah Suhendra (Ma Chung Press, 2019)
This review focuses on characterization and the idea of compassionate love. The writer conducted the study to explain the compassionate love seen through the characterization of the main characters in Me Before You movie, Will Traynor and Louisa Clark. The writer uses P.A.R.T.S. characterization theory by Reams (2015) and compassionate love theory by Fromm (1995), Underwood (2002, 2009) and Stenberg (1986) to analyze the two main characters. The analysis uses descriptive qualitative method. The findings of the analysis show P.A.R.T.S. characterization of both main characters. There are seven characteristics of compassionate love seen through the characterization of the main characters. It is seen that Will is a stubborn and strong-willed man, yet he still has that romantic side to show his love which centers on the good of others. Louisa is seen as a persistent and sincere woman who works as Will’s caregiver that later falls in love with Will and show how she can make him happy and give him freedom. The P.A.R.T.S. characterization of Will Traynor and Louisa Clark shows the kind of love which centers on the good of the other, i.e. compassionate love.